Environmentally Toxic Solid Nanoparticles in Noradrenergic and Dopaminergic Nuclei and Cerebellum of Metropolitan Mexico City Children and Young Adults with Neural Quadruple Misfolded Protein Pathologies and High Exposures to Nano Particulate Matter - Lilian Calderón-Garcidueñas; Angélica González-Maciel; Rafael Reynoso-Robles; Héctor G. Silva-Pereyra; Ricardo Torres-Jardón; Rafael Brito-Aguilar; Alberto Ayala; Elijah W. Stommel; Ricardo Delgado-Chávez (Toxics, 2022)
Quadruple aberrant hyperphosphorylated tau, beta-amyloid, α-synuclein and TDP-43 neuropathology and metal solid nanoparticles (NPs) are documented in the brains of children and young adults exposed to Metropolitan Mexico City (MMC) pollution. We investigated environmental NPs reaching noradrenergic and dopaminergic nuclei and the cerebellum and their associated ultrastructural alterations. Here, we identify NPs in the locus coeruleus (LC), substantia nigrae (SN) and cerebellum by transmission electron microscopy (TEM) and energy-dispersive X-ray spectrometry (EDX) in 197 samples from 179 MMC residents, aged 25.9 ± 9.2 years and seven older adults aged 63 ± 14.5 years. Fe, Ti, Hg, W, Al and Zn spherical and acicular NPs were identified in the SN, LC and cerebellar neural and vascular mitochondria, endoplasmic reticulum, Golgi, neuromelanin, heterochromatin and nuclear pore complexes (NPCs) along with early and progressive neurovascular damage and cerebellar endothelial erythrophagocytosis. Strikingly, FeNPs 4 ± 1 nm and Hg NPs 8 ± 2 nm were seen predominantly in the LC and SN. Nanoparticles could serve as a common denominator for misfolded proteins and could play a role in altering and obstructing NPCs. The NPs/carbon monoxide correlation is potentially useful for evaluating early neurodegeneration risk in urbanites. Early life NP exposures pose high risk to brains for development of lethal neurologic outcomes. NP emissions sources ought to be clearly recognized, regulated, and monitored; future generations are at stake.